Establishment and Characterization of an Embryonic Cell Line from Sarconesiopsis magellanica - Cruz, Mónica (University of Wisconsin Library, 2013)
Sarconesiopsis magellanica (Le Guillou) (Diptera: Calliphoridae) is a necrophagous fly that is important in both human and veterinary medicines. This insect has been registered in Colombia as a biological indicator in estimating post-mortem interval. Insect cell cultures are an important biotechnological tool for basic and applied studies, and cell cultures derived from S. magellanica embryonic tissues are described in this study. S. magellanica embryonated eggs were taken for tissue explants. These were seeded in L-15, Grace/L-15, Eagle MEM, MM, VP12, MM/VP12, and Schneider culture media. The morphological, cytogenetic, biochemical, and molecular characteristics of the cell cultures were examined. Cell growth was achieved in the L15, Grace/L15, and Schneider culture media, and the confluent monolayers were obtained 8, 10, and 19 days after the embryonated eggs were explanted. However, the Schneider medium was the most efficient to develop the subcultures, and 21 passages have been maintained. The cell morphology of the primary cell cultures was initially heterogeneous, but in the confluent monolayer and in the subcultures there was greater cell morphology uniformity, fibroblastoid types being predominant. Cultured cells had a chromosomal number of 12, and the karyotypic complement consisted of five pairs of somatic chromosomes and one sexual pair. The cell culture isozyme patterns of S. magellanica coincided with adult samples from the same species. The molecular analysis, using RAPD-PCR, demonstrated the authentication of the cell cultures of this fly and their differentiation from other cultures derived from two sand flies species. This cell line is a new in vitro model that will be used in biomedical and biotechnological studies.